Novel Graphene Oxide/Quercetin and Graphene Oxide/Juglone Nanostructured Platforms as Effective Drug Delivery Systems with Biomedical Applications - Alexa-Maria Croitoru; Alina Moroșan; Bianca Tihăuan; Ovidiu Oprea; Ludmila Motelică; Roxana Trușcă; Adrian Ionuț Nicoară; Roxana-Cristina Popescu; Diana Savu; Dan Eduard Mihăiescu; Anton Ficai (Nanomaterials, 2022)
In this paper, novel drug delivery systems (DDS) were designed based on graphene oxide (GO) as nanocarrier, loaded with two natural substances (quercetin (Qu) and juglone (Ju)) at different concentrations. The chemical structure and morphology of the synthesized GO-based materials were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and Raman spectroscopy. The antibacterial activity was evaluated against standard strains, Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 8739, and Candida albicans ATCC 10231. Results demonstrated excellent antimicrobial activity, with a 5 log reduction of E. coli and a 1 log to 3.04 log reduction of S. aureus populations. Reduction rates were above 90%. Biocompatibility tests were also performed on GO-based materials, and the results showed biocompatible behavior for both L929 fibroblast cell line and BT474 breast cancer cells at lower concentrations. The identity of Qu and Ju was demonstrated by matrix-assisted laser desorption/ionization (MALDI) analysis, showing the compounds’ mass with high accuracy. In addition, specific properties of GO made it a versatile matrix for the MALDI analysis. The results of this study indicated that GO-based platforms may be suitable for applications in many areas for the effective and beneficial use of hydrophobic compounds such as Ju and Qu.